Pegaruh media kreatif pop up terhadap keterampilan membaca siswa kelas III SDN Kebodalem Mojosari. - Devita Aryana Putri; Rarasaning Satianingsih; Via Yustitia; Danang Prasetyo (PPPM STKIP PGRI Lamongan, 2022)
The reading skills of students in Indonesia every year always decline, this is evidenced by the PISA score on reading literacy. The teacher must make appropriate media for the learning process. Pop Up is a book that has a movable part or a three-dimensional element that contains the element of interaction when opened as if there were objects coming out of the book. The purpose of this study was to determine the effect of Pop Up media on the reading skills of students in class III Theme 4 Subtheme 1 Learning 1 SDN Kebondalem Mojosari. This research is a quantitative research type Quasi-experimental design. The design used is the Posttest Only Control Design. Data collection techniques used are using tests and documentation. The data analysis technique uses inferential statistics then the normality test, homogeneity test, balance test, and t-test with SPSS 22.0 assistance. The results showed that there was an influence of the Pop Up media on the reading skills of students in class III Theme 4 Subtheme 1 Learning 1 SDN Kebondalem Mojosari.